2021
DOI: 10.1021/acscatal.0c05356
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Profiling of a Pd/Al2O3 Catalyst during Selective Ammonia Oxidation

Abstract: The utilization of operando spectroscopy has allowed us to watch the dynamic nature of supported metal nanoparticles. However, the realization that subtle changes to environmental conditions affect the form of the catalyst necessitates that we assess the structure of the catalyst across the reactant/product gradient that exists across a fixed bed reactor. In this study, we have performed spatial profiling of a Pd/Al 2 O 3 catalyst during NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 48 publications
5
35
0
Order By: Relevance
“…1). This initiated at the outlet of the catalyst bed and propagated towards the inlet, as is consistent with other spatially resolved studies 23,27,28 . Interestingly, we were able to observe oscillatory behaviour in the end pipe MS analysis, the intensity of adsorbed carbonyl bands through DRIFTS, and the intensity of the XANES white line at each spatial position (Supplementary Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1). This initiated at the outlet of the catalyst bed and propagated towards the inlet, as is consistent with other spatially resolved studies 23,27,28 . Interestingly, we were able to observe oscillatory behaviour in the end pipe MS analysis, the intensity of adsorbed carbonyl bands through DRIFTS, and the intensity of the XANES white line at each spatial position (Supplementary Fig.…”
Section: Resultssupporting
confidence: 90%
“…In particular, Dann et al were able to follow the kinetic oscillations of CO oxidation over Pd/Al2O3 and found that only the inlet of the reactor influenced the end-pipe mass spectrometry (MS) oscillations 23 . This need for spatial analysis during spectroscopic investigations is often overlooked, i.e., which point of a catalytic fixed-bed reactor truly contributes to the oscillatory behaviour [27][28][29][30] and can provide crucial information which are often missing in the commonly employed single point analysis.…”
Section: Localised Thermal Levering Events Drive Spontaneous Kinetic ...mentioning
confidence: 99%
“…Catalysts play an important role in many industries, especially in the chemical industry, which can be divided into homogeneous catalysts and heterogeneous catalysts. Although homogeneous catalysts often have higher catalytic activity, they are difficult to recover from the reaction solution, so their industrial application is limited. , In contrast, heterogeneous catalysts (such as supported catalysts) can be easily separated from the reaction solution and reused many times, which have been paid much attention and applied in different reaction systems like hydrogenation, oxidation, ammonia oxidation, and hydroxylation . Various solid supports like Al 2 O 3 , TiO 2 , CeO 2 , metal–organic frameworks (MOFs), zeolitic imidazolate frameworks (ZIFs), and ceramic membranes have been developed for fabricating heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an appearance of hydrazine species (intermediates in the hydrazine mechanism) on the ammonia pre-adsorbed Pd-Y catalyst at 250 • C during FT-IR studies, suggested that the ammonia oxidation is more complicated and followed different parallel routes. Otherwise, Wells et al [46,47] identified PdN x under reaction conditions over H 2 -reduced (1.5 wt.%)Pd/Al 2 O 3 and Pd/Y (n(Si)/n(Al) = 2.6) as the dominant species during N 2 formation (based on combined operando spectroscopy and DFT calculations). As stated above, palladium-containing materials appear as promising NH 3 -SCO catalysts, although, their stability (also in the presence of H 2 O, SO x, and CO x ) needs confirmation.…”
Section: Pt-and Pd-based Catalystsmentioning
confidence: 99%